Uptake of atmospheric hydrogen by soils: a case study from southern Poland. (1st July 2013) - Bartyzel, J.; Necki, J. M.; Zieba, D.; Rozanski, K.; Gasiorek, M.
Summary Uptake of atmospheric hydrogen by soils constitutes the most important sink of this gas at the global scale. However, little is known about the strength and spatio‐temporal variability of this sink. We present the results of a systematic study aimed at characterizing hydrogen uptake by urban soils. The study was carried out at two field sites in Krakow, southern Poland. The measured fluxes of hydrogen to soils revealed distinct seasonality, with large values (up to 40 µmol hour−1 m−2) recorded during summer months and small values (between 5 and 10 µmol hour−1 m−2) during winter. Temperatures in the top 6 cm of the soil profile varied during the study from −9 to +24°C, while volumetric soil water content fluctuated between 15 and 50%. Measurable hydrogen fluxes were also observed when soil temperatures were less than zero. The results were interpreted in the context of seasonal changes of local climate and air and soil temperature, soil water content and amount of rainfall. Mixing conditions at the air–soil interface were also considered. Modelling of H2 uptake was performed with a two dimensional diffusion transport model, with contrasting assumptions about distribution and intensity of the hydrogen sink in the soil profile. The model results suggest that conditions in the uppermost soil layer exert a decisive control on measured hydrogen uptake rates. The measured hydrogen flux can be reproduced by the transport model only if significant reduction of the soil water content in the uppermost layer of the soil is postulated. This finding has important implications for the parameterization of hydrogen uptake rates in models of the global H2 budget.